2011
DOI: 10.1158/1538-7445.am2011-2665
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2665: NBTXR3 hafnium oxide nanoparticle activated by ionizing radiation demonstrates marked radio-enhancement and antitumor effect via high energy deposit in human soft tissue sarcoma

Abstract: Local and systemic control of Soft Tissue Sarcoma (STS) remains a clinical challenge. Radiation therapy is part of the standard of care of STS. The narrowness of its therapeutic window represents the main concern for different clinical settings. Thus, local delivery of radiation doses is critical to ensure optimal benefit-risk ratio. NBTXR3, biocompatible hafnium oxide nanoparticles were designed as therapeutics to be activated by ionizing radiation to achieve tumor control by enhancement of local energy depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…NBTXR3 were designed for direct local intratumoral injection and subsequent radiosensitization 6 , 137 . Subsequently, it has been demonstrated by Monte Carlo simulation that NBTXR3 crystalline nanoparticles exposed to high-energy photons could promote a significant radiation dose enhancement, and the obvious radiosensitizing effects of NBTXR3 in vitro and in vivo were presented 138 - 140 . Also, nonclinical toxicology evaluation of this agent showed a good tolerance.…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…NBTXR3 were designed for direct local intratumoral injection and subsequent radiosensitization 6 , 137 . Subsequently, it has been demonstrated by Monte Carlo simulation that NBTXR3 crystalline nanoparticles exposed to high-energy photons could promote a significant radiation dose enhancement, and the obvious radiosensitizing effects of NBTXR3 in vitro and in vivo were presented 138 - 140 . Also, nonclinical toxicology evaluation of this agent showed a good tolerance.…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…It was reported that nanoparticles with surface charge corresponding to a potential less than 20 mV can provide sufficient stabilization when using large molecular weight stabilizers (PEG-diamine), which act mainly by steric stabilization [46]. Moreover, to investigate the stability of Pt NFs in aqueous solution with different pH values (3)(4)(5)(6)(7)(8)(9)(10)(11), the sizes and zeta potential of Pt NFs were studied (see supporting information Figure S1). The hydrodynamic diameter of Pt NFs remained similar as the pH changes, with no visible precipitation.…”
Section: Synthesis and Characterization Of Pt Nfsmentioning
confidence: 99%
“…Nanoparticles containing other heavy elements, for example, 50-nm crystalline HfO2 NPs (NBTXR3, Nanobiotix, Paris, France), were also developed. It has been demonstrated that these NPs exposed to high-energy photons induce a significant radiation dose enhancement as shown in vitro and in vivo [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The free radicals generated by the electrons ejected from the metal-based NP and from water are highly reactive and tend to break the covalent bonds of molecules they encounter. In fact, an increase in cell death mechanisms such as apoptosis, necrosis and autophagy has been demonstrated when irradiated cells enter into contact with NP [ 2 ]. Nanoparticles with a physical mode of action were able to enhance pathway activity of cancer cells via increased DNA damage, compared to RT alone [ 3 ].…”
Section: Radio-enhancement By Npmentioning
confidence: 99%